Training on the Production of Chitosan Fish Preservatives (PETASAN) and Digital Marketing for Fish Traders in Kalanganyar Village - A’yunil Hisbiyah; Eviomitta Rizki Amanda; Suryo Hadi Kusumo; Martina Kurnia Rohmah (Unram Journal of Community Service, 2025)
Kalanganyar Village is a village located at the eastern tip of Sidoarjo Regency. Geographically, Kalanganyar Village borders directly on the sea, so almost 2/3 of the area of ​​Kalanganyar Village is aquaculture area. Most of the residents' livelihoods are subsistence farming and fish trading. The problems faced by village residents are related to food security and marketing management. Therefore, there is a need for training on fish preservatives made from natural ingredients, namely chitosan, and digital-based marketing for fish traders. The method for implementing this activity is the Participatory Rural Appraisal method; a group of fish traders are involved in planning and carrying out this community service activity. This activity improved the quality of fish products by using chitosan-based preservatives, increasing product hygiene, and increasing skills in conducting digital marketing using the help of artificial intelligence. From this activity, a plucking thorn group and a mundak bati group were also produced, which had a governance organizational structure so that the operational management of the group was more structured and neat, both of which were approved by a decree from the Head of Kalanganyar Village.